2022
DOI: 10.2196/28323
|View full text |Cite
|
Sign up to set email alerts
|

Barriers to and Facilitators of Automated Patient Self-scheduling for Health Care Organizations: Scoping Review

Abstract: Background Appointment management in the outpatient setting is important for health care organizations, as waits and delays lead to poor outcomes. Automated patient self-scheduling of outpatient appointments has demonstrable advantages in the form of patients’ arrival rates, labor savings, patient satisfaction, and more. Despite evidence of the potential benefits of self-scheduling, the organizational uptake of self-scheduling in health care has been limited. Objec… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 90 publications
0
17
0
Order By: Relevance
“…Among the included reviews, there was no evidence of the impact of gender and sex on access to digital health. Of the 22 reviews, 8 (36%) reviews reported on the impact of gender and sex on the use of digital technology, with 4 (18%) reviews indicating consistent evidence of a greater use of digital health technology among women [ 22 , 31 , 35 , 37 ]. Of the remaining 18% (4/22) of reviews, 2 observed no difference in use by gender and sex [ 4 , 21 ] and 2 reported mixed evidence [ 32 , 39 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Among the included reviews, there was no evidence of the impact of gender and sex on access to digital health. Of the 22 reviews, 8 (36%) reviews reported on the impact of gender and sex on the use of digital technology, with 4 (18%) reviews indicating consistent evidence of a greater use of digital health technology among women [ 22 , 31 , 35 , 37 ]. Of the remaining 18% (4/22) of reviews, 2 observed no difference in use by gender and sex [ 4 , 21 ] and 2 reported mixed evidence [ 32 , 39 ].…”
Section: Resultsmentioning
confidence: 99%
“…The association between education and access to digital health was not reported in any of the reviews. However, 18% (4/22) of reviews reported a possible association between the use of digital health care and education showing that individuals with higher levels of education were more likely to use digital health services than individuals with a lower education level [ 18 , 21 , 29 , 35 ]. Only 5% (1/22) of reviews reported inconclusive evidence [ 32 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Patients may benefit significantly from optimized scheduling of online care, as Luxenburg et al shows how older and more ill patients are less likely to schedule appointments when the process is difficult ( 17 ). Further research supports the importance of online self-scheduling in empowering patient-centered care and satisfaction while providing advantages to traditional phone scheduling ( 18 , 19 ).…”
Section: Discussionmentioning
confidence: 73%
“…A recent review explored barriers and facilitators of patient self-scheduling in health care; however, none of the studies included in the review mentioned usability testing. 46 Considering low technology adoption and digital literacy among certain groups, 16 , 18 , 47 involving these users early in the design process is imperative. Similar to our study, the review of patient self-scheduling in health care did identify trust in the system as 1 factor which would impact use.…”
Section: Discussionmentioning
confidence: 99%